Language Constrain in Academic Writing in The Form of Thesis For Students of Letters Faculty of Universitas Muslim Indonesia Makassar - Kaharuddin Nemba (Seltics Journal: Scope of English Language Teaching Literature and Linguistics, 2023)
This research aims to describe the students’ dominant influence in writing their thesis and the factors they faced in writing their thesis. The method of the study was library research, which meant that the researcher only collected data from their thesis, which was under the researcher’s supervision, and students tested in the thesis examination. The population of this research was all language aspects in the language constraints in academic writing. Because the language aspects are too large, the researcher limited the sample using a purposive sample technique, such as diction, effective sentences (coherence and parallelism), conjunctions, punctuation, and paragraphs (open, main, and closed). Then, the techniques for collecting data were observation, noting, and documentation. Those data were taken from 21 students writing their thesis and tested in the thesis examination. The result of this research was the dominant students' influence in writing their thesis was to compose effective sentences, chose exact words (diction), used conjunction, and made/built open and closed paragraphs. The factors that made it them were students' less practiced writing, less reading, and only depending on their lecture